Microplastics as hubs enriching antibiotic-resistant bacteria and pathogens in municipal activated sludge - Pham, Dung Ngoc; Clark, Lerone; Li, Mengyan (Journal of hazardous materials letters, 2021)
[Display omitted] •Microplastics can enrich antibiotic resistant genes from municipal activated sludge.•Microplastics carry bacteria that are pathogenic to human and natural biota.•The highly abundant Novosphingobium and Flectobacillus may contribute to plastisphere formation.•Surface hydrophobicity of microplastics promotes acclimation of biofilms. Microplastics can serve as carriers of antibiotic-resistant bacteria (ARB) and pathogens, representing a pressing concern to aquatic biota and human health. Activated sludge units at municipal wastewater treatment plants (WWTPs) are “hotspots” converging microplastics and antibiotics. In this batch study with activated sludge samples from three domestic WWTPs, we demonstrated both polyethylene (PE) and polystyrene (PS) microplastics can acclimate biofilms enriched with sulfonamide resistance genes (sul1 and sul2) and the associated mobile genetic element (intI1) in comparison with fine sands as control particles. Absolute abundances of these genes were further elevated by 1.2∼4.5 fold when sulfamethoxazole was initially spiked as a representative sulfonamide. The combination of 16S rRNA amplicon sequencing and differential ranking analysis revealed that microplastics selectively promoted antibiotic-resistant and pathogenic taxa (e.g., Raoultella ornithinolytica and Stenotrophomonas maltophilia) with enrichment indices ranging from 1.6 to 3.3. Furthermore, heterotrophic Novosphingobium and filamentous Flectobacillus accounted for 14.6 % and 3.3 % on average in microplastic biofilms, respectively, which were up to 2.8 and 11.1 times higher than those in sand biofilms. Dominance of these bacterial species may contribute to initial biofilm formation that facilitates subsequent colonization and proliferation of ARB and pathogens, thus amplifying their risks in the receiving environments and beyond.